Time for Silence to End - F. Todd Goodson (Educational Considerations, 2019)
This issue of Educational Considerations explores the complex territory where teachers meet children impacted by trauma. Human traumatic experience is a topic that has been underreported, unacknowledged, and misunderstood for too long by too many. As we confront trauma, we quickly come to the realization that all teachers at all levels need a better understanding of the scope and impact of trauma on their classrooms and pedagogical strategies grounded in our best available understanding of the needs of all students.
Keywords: Trauma; Teaching